2015
DOI: 10.1007/s00531-015-1155-5
|View full text |Cite
|
Sign up to set email alerts
|

Types of soft-sediment deformation structures in a lacustrine Ploužnice member (Stephanian, Gzhelian, Pennsylvanian, Bohemian Massif), their timing, and possible trigger mechanism

Abstract: facies associations preserve from 22.5 to 20.5 cm SSDS/m, and in palustrine carbonate, 13.5 cm mechanical SSDS/m was found. SSDS in fluvial facies are rare (2.9 cm SSDS/m). The distribution of SSDS in the Sm-1 borehole shows clear relationships to sedimentary facies and processes such as density flows or fluctuation of water level. The relationships of particular structures indicate a relative timing of formation which is as follows: sediment deposition was followed by the formation of mechanical SSDS, then by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…SU7 records high sediment accumulation rates in a subaqueous environment. The large scale deformation features that gradually transition upwards into dish structures and ripple-scale crosslamination suggest rapid deposition, loading and dewatering for the bulk of the unit (Stárková et al 2015;Winsemann et al 2015). Consistent north and northwestward paleoflow directions indicate sediment delivery from the south, and combined with the incorporation of shell fragments and other organic debris, indicate erosion and resedimentation of pre-existing sandy sediments (e.g., SU4-SU6).…”
Section: Su7: Rippled and Deformed Fine-grained Sandmentioning
confidence: 99%
See 1 more Smart Citation
“…SU7 records high sediment accumulation rates in a subaqueous environment. The large scale deformation features that gradually transition upwards into dish structures and ripple-scale crosslamination suggest rapid deposition, loading and dewatering for the bulk of the unit (Stárková et al 2015;Winsemann et al 2015). Consistent north and northwestward paleoflow directions indicate sediment delivery from the south, and combined with the incorporation of shell fragments and other organic debris, indicate erosion and resedimentation of pre-existing sandy sediments (e.g., SU4-SU6).…”
Section: Su7: Rippled and Deformed Fine-grained Sandmentioning
confidence: 99%
“…4,5,11,16,17) that impedes downward migration of the surface contaminants. Spoelstra et al (2017) showed that water extracted from many domestic wells penetrating the Lake Algonquin Sand Aquifer and groundwater seeps along the river contain artificial sweeteners, likely derived from rural septic systems in the sand plain. Further testing of water chemistry in shallow and more deeply buried aquifers may assist in determining the potential connection between aquifer systems in the region.…”
Section: Groundwater Applicationsmentioning
confidence: 99%
“…Its lithostratigraphical equivalent, the Ploužnice Horizon, is situated in the southern part of the basin and also consists of two lacustrine horizons several tens of meters thick. Typical are varicoloured pale grey, violet and red siltstones and claystones with a high content of redeposited volcanic ashes, ripple bedded sandstones, intercalated red cherts and in situ pyroclastics (Prouza and Tásler 2001, Opluštil et al 2013, 2016b, Stárková et al 2015. The newly discovered fossiliferous locality in the Ploužnice Horizon is situated on the south-eastern border of Ploužnice village in a small ravine on a forested slope on the left side of the road leading to the village of Bradlecká Lhota.…”
Section: Geological Setting and Taphonomymentioning
confidence: 99%
“…Car bon if er ous/Perm ian lac us trine shales are com mon in Cen tral Eu rope. They oc cur, for ex am ple, in the Bo he mian Mas sif of the Czech Re pub lic (Martinek et al, 2006;Lojka et al, 2009Lojka et al, , 2010Stárková et al, 2015) and in Po land in the Sudetes (Dziedzic, 1959(Dziedzic, , 1961Mastalerz and Wojewoda, 1988;Mastalerz, 1990;Mastalerz and Nehyba, 1997). Based on their geo log i cal struc ture, the Sudetes are con sid ered an un prom ising re gion for the oc cur rence of hy dro car bon de pos its.…”
Section: Introductionmentioning
confidence: 99%